2016
DOI: 10.5009/gnl15042
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Adalimumab in Moderately to Severely Active Cases of Ulcerative Colitis: A Meta-Analysis of Published Placebo-Controlled Trials

Abstract: Background/AimsTo evaluate the efficacy and safety of adalimumab (ADA) in moderately to severely active ulcerative colitis (UC) patients who are unresponsive to traditional therapy.MethodsElectronic databases, including the PubMed, Embase, and Cochrane databases, were searched to April 20, 2014. UC-related randomized controlled trials (RCTs) that compared ADA with placebo were eligible. Review Manager 5.1 was used for data analysis.ResultsThis meta-analysis included three RCTs. ADA was considerably more effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…The impact or need for combination therapy with adalimumab and immunomodulators has been debated and the results are diverging. Zhang et al presented a metaanalysis including three randomized clinical trials indicating combination therapy to be superior to adalimumab monotherapy [27]. However, exploratory post hoc analyses of the ULTRA 1 and ULTRA 2 studies by Colombel et al did not show any advantage with combination therapy [28].…”
Section: Discussionmentioning
confidence: 99%
“…The impact or need for combination therapy with adalimumab and immunomodulators has been debated and the results are diverging. Zhang et al presented a metaanalysis including three randomized clinical trials indicating combination therapy to be superior to adalimumab monotherapy [27]. However, exploratory post hoc analyses of the ULTRA 1 and ULTRA 2 studies by Colombel et al did not show any advantage with combination therapy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several MAs 9,13,14,16,[18][19][20]24,25,27,29,[31][32][33][35][36][37][38][39] provided heterogeneity assessment. Most comparisons versus placebo did not show substantial heterogeneity 16,24,32,36 (Table 1A-D). In many cases, MAs included only one study or fewer than 10 studies, thus tests for small-study effects were not applicable.…”
Section: Methodsmentioning
confidence: 99%
“…3,8,12,[15][16][17][18][19] Adalimumab, a fully human monoclonal antibody that targets TNF-α, was proven to be effective and safe in clinical trials of up to 4 years in patients in Western countries with moderate to severe UC who were unresponsive to traditional treatments or discontinued therapy because of safety concerns. 8,12,16,17,[19][20][21][22] In addition, results from a 52-week, phase 2/3, randomized, double-blind study demonstrated the safety and efficacy of adalimumab (an initial subcutaneous injection of 160 mg, followed by 80 mg at 2 weeks, then 40 mg every other week from week 4 through 52 [160/80-mg schedule]) in anti-TNF-naive Japanese patients with moderate to severe UC who were refractory to corticosteroids, immunomodulators, or both. 18 Furthermore, an open-label extension of this study in 190 patients reported that the efficacy of adalimumab was maintained for up to 4 years, with no new safety signals identified.…”
Section: Introductionmentioning
confidence: 99%